The Effects of Low-Quality University Education on Young Graduated Labour Outcomes: The Peruvian Experience - Raygada Mimbela, Adriana Cristina (2023)
This thesis examines the relationship between university education quality and young graduates' labour outcomes. The thesis employs a micro-level data analysis based on the National Survey of Households (ENAHO) and information from the National Board of University Education (SUNEDU). Linear Probability Models and an OLS multivariate regression are used to assess the effects of the quality university in four labour outcomes: not in employment, education or training (NEET), employment, informal occupation, and income. The findings reveal that lowquality universities among young graduates are not associated with a higher likelihood of being NEET or employed. However, there is a significant relationship between the quality of the university and informal occupation and income outcomes.